ANALISIS PENERAPAN AKUNTANSI PENDAPATAN BERDASARKAN PSAK 72 - Nuraini, Fitri; Melynda Sari, Tyasha Ayu (Jurnal Akuntansi Muhammadiyah (JAM), 2024)
The purpose of this study is to examine the income earned on online marketplace sales transactions according to PSAK 72. Starting from the process of recognizing and measuring revenue to presenting and disclosing it in the financial statements.The method used in this study is a qualitative method with a field study and literature study approach.The data processed is data that comes from observations, interviews, and documentation in the form of marketplace contracts, details of sales transactions for the February 2023 period, checking accounts, and financial reports for the February 2023 period. The results of the study show that the recognition and measurement of income carried out by PT XYZ has notin accordance with PSAK 72. This is because PT XYZ recognizes and records its revenue when an order is made, whereas according to PSAK 72 revenue can be recognized and recorded when the performance obligation has been declared complete.Besides that, PT XYZ also measures its income based on the selling price, not based on the transaction price.In the statement of changes in financial position, income that has not been received by PT XYZ is recognized as cash, whereas in PSAK 72 if the entity has completed its performance obligation, the amount of consideration that will become the right of the entity must be recognized and recorded as a contract asset.